The Role of Blockchain Technology in the Security and Privacy of Healthcare Information System Data: Literature Study - Pratiwi, Irra; Widodo, Suprih; Abdulmajid, Nuur Wachid (Department of Information Technology, Universitas Timor, Indonesia, 2024)
The growing interest in digitization is driving the increasing use of patient identity storage and medical records by healthcare providers. By applying the concept of decentralization and data distribution, blockchain provides a solution to protect highly sensitive health information from the risk of cyberattacks and data manipulation, which is very prevalent. In addition, blockchain also has the key to authenticating patient identity and creating secure medical history tracking. The method used in this research is a literature study to explore literature from various journals and articles related to the role of blockchain technology in improving the security and privacy of health information system data. Therefore, this research can provide an in-depth understanding of the positive impacts and potential challenges in implementing blockchain technology for health information system data security. Blockchain technology can help reduce the occurrence of data loss or fraud, reduce hospital inventory costs, and can quickly integrate disparate systems.